Exercise Prescription in Cardiac Rehabilitation A Practical Approach to Early Mobilization and Exercise Training - Staron, Adam; Wolszakiewicz, Jadwiga; AlSulaimi, Meteb (MDPI Books, 2022)
This book has been reviewed by two (or more) external single-blind reviewers. The opinions expressed in the book do not reflect the view of the publisher. ...read more Keywords: cardiac rehabilitation, exercise prescription, interval training